Teachers’ Perspectives on Inclusive Education Practices in East Kutai Regency: Persepsi Guru tentang Praktik Pendidikan Inklusif di Kabupaten Kutai Timur - Baga, Vinsensius Susanto; Sukinah (Indonesian Journal of Innovation Studies, 2025)
background: Inclusive education is a national mandate requiring schools to provide equitable learning opportunities for all students. Specific background: In East Kutai Regency, schools are transitioning toward inclusive practices despite structural and resource limitations. Knowledge gap: Limited empirical evidence exists regarding teachers’ perspectives as key actors in implementing inclusive education in this region. Aims: This study investigates teachers’ perceptions of conceptual understanding, school readiness, supporting and limiting factors, personal competencies, and expectations for inclusive education development. Results: Findings show that teachers hold positive conceptual awareness but report insufficient facilities, limited special education personnel, high administrative workload, and gaps in practical competencies, particularly in designing individualized learning programs. Training participation is strongly associated with higher levels of readiness, confidence, and use of supportive strategies. Novelty: This study integrates multilevel analysis of teachers’ perceptions based on training, experience, and institutional conditions within a geographically diverse district. Implications: Strengthening continuous professional development, improving support services, and enhancing policy consistency are essential to advancing inclusive education implementation across East Kutai. Highlights Teachers show strong conceptual understanding but face limited structural support. Training emerges as the most influential factor shaping teacher preparedness. Schools require better facilities, personnel, and policy alignment to sustain inclusivity. Keywords Inclusive Education, Teacher Perspectives, School Readiness, Educational Services, Learning Support